Ultra-Processed Foods and it’s Association With Blood Pressure Among Outpatients At PMC Hospital - Anggraini, Shelly; Anugerah Humairah; Restu Sakinah; Ariati, Miftah (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Background: Hypertension prevalence worldwide increased to 33% in 2023. According to the 2023 Indonesian Health Survey (SKI), Riau Province ranked 27th among all provinces, with a hypertension prevalence of 25.4%. Ultra-processed food (UPF) consumption is a known risk factor for hypertension and other non-communicable diseases, as UPFs typically contain high levels of sodium, sugar, and fat. However, limited studies have investigated the association between UPF consumption and blood pressure. Aim: This study aimed to examine the association between UPF consumption patterns and blood pressure among outpatients at PMC Hospital. Method: A cross-sectional study was conducted with 86 respondents. Primary data were collected, including UPF consumption frequency and blood pressure measurements. Results: No significant association was found between UPF consumption and systolic blood pressure (p = 0.088). However, a significant association was observed between UPF consumption and diastolic blood pressure (p = 0.024). Conclusion: UPF consumption is significantly associated with diastolic blood pressure. Frequent UPF intake contributes to elevated diastolic blood pressure in patients with hypertension